The occurrence of self-reported illnesses and their analyses into influenza-like and gastrointestinal syndromes in a rural community in Western Kenya, 2019 - Chweya, Reagan N.; Mambo, Susan N.; Gachohi, John M. (International Journal Of Community Medicine And Public Health, 2021)
Background: Data-driven population studies focusing on clinical symptoms and syndromes with the potential to improve diagnostic strategies are rare in Africa. The objective of the study was to determine the prevalence of influenza-like illness (ILI) and gastrointestinal (GI) syndromes in a rural community in western Kenya. Methods: Using a cross-sectional study design, we collected data on self-reported symptoms experienced during the week preceding the study and clustered them into syndromes using case definitions in western Kenya. The study randomly enrolled 92 households and recruited 390 subjects aged between 5 and 83 years. On one hand, reporting at least any four prespecified respiratory-related symptoms attained influenza-like illness (ILI) syndrome while on the other, gastrointestinal (GI) syndrome constituted the reporting of at least any three of prespecified GI system symptoms. Data on individual and household-level independent variables were collected using interviewer-administered questionnaires. Using multivariable logistic regression models, we assessed relationships between the occurrence of these syndromes and the independent variables at a significance level of p≤0.05. Results: Respectively, 27% and 9% of subjects attained ILI and GI syndromes. Twenty-four subjects attained both syndromes. Visiting outside the local sub-county of residence was associated with attaining ILI (OR=2.3, 95% CI 1.4, 3.7) and GI syndromes (OR=3.4, 95% CI 1.6, 6.9). Besides, the absence of active medical insurance was independently associated with attaining GI syndrome (OR=0.12, 95% CI 0.02, 0.94). Conclusions: Study findings suggested the existence of a higher burden of ILI relative to GI syndrome making the study area critical for investigating disease exposures related to visiting outside the study area and the link between medical insurance and ill health occurrence.